2020
DOI: 10.21203/rs.3.rs-82662/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlations of IL-6, IL-6R, IL-10 and IL-17 gene polymorphisms with the prevalence of COVID-2019 infection and its mortality rate 

Abstract: The pathogenesis of COVID-19 implicates a potent inflammatory response resulting in cytokine storm. We aimed to evaluate association between polymorphisms in IL-6 gene at rs1800796/rs1800795, IL-6R at rs2228145, IL-10 at rs1800896 and rs1800871, IL-17 at rs2275913 and rs76378, and the prevalence (per million) and mortality rates (per million) of COVID-19 among populations of China, Japan, India, Iran, Spain, Italy, Mexico, Netherlands, Sweden, Turkey, Finland, Brazil, Czechia, Russia, Poland. AG and GG genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In a study conducted by Batur & Hekim, 2021, the diversities of IL-17A gene polymorphism at rs2275913 locus showed that the populations of China, Japan, Iran, Finland, Czechia, India, Norway, and Poland mostly have the AG genotype, while populations of Spain, Mexico, Netherlands, Turkey, Brazil, Germany, Tunisia, Egypt, and Croatia the GG genotype. 11 We investigated the association of the IL-17A genotypes with the disease severity of COVID-19. There was no significant association between the frequencies of the genotypes and the disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study conducted by Batur & Hekim, 2021, the diversities of IL-17A gene polymorphism at rs2275913 locus showed that the populations of China, Japan, Iran, Finland, Czechia, India, Norway, and Poland mostly have the AG genotype, while populations of Spain, Mexico, Netherlands, Turkey, Brazil, Germany, Tunisia, Egypt, and Croatia the GG genotype. 11 We investigated the association of the IL-17A genotypes with the disease severity of COVID-19. There was no significant association between the frequencies of the genotypes and the disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study by Batur & Hekim, 2021, observed that the frequencies of IL-17 gene polymorphisms may not directly correlate with the course and severity of COVID-19 infection. 11 On the other hand, a study by Xie et al, 2019, reported that compared with individuals carrying the wildtype GG genotype of rs2275913 at IL-17, the AA-homozygous and GA-heterozygous individuals were protected from the development of ARDS. Consistently, a decreased 30-day mortality risk was found among A-allele carriers of rs2275913 at IL-17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One preprint compares the frequency of rs1800796 and rs1800795 of IL-6, rs2228145 of IL-6R, rs1800896 and rs1800871 of IL-10, rs2275913 of IL-17A and rs76378 of IL-17F as recorded in previous studies with the prevalence/10 6 population and mortality/10 6 population of COVID-19 in China, Japan, India, Iran, Spain, Italy, Mexico, Netherlands, Sweden, Turkey, Finland, Brazil, Czechia, Russia, Poland, suggesting a possible role for rs2275913 of IL-17A in COVID-19 prevalence and mortality [159][160][161][162]. This piece of data is particular intriguing, assuming that the analyzed polymorphism is reported as associated with susceptibility to cutaneous and airway infections, ARDS and asthma [163][164][165][166][167][168][169].…”
Section: Other Cytokines Chemokines and Their Signaling Pathwaysmentioning
confidence: 94%